Chosen Glory and Chosen Trauma with Chinese Characteristics: Social Representations of History in an Authoritarian Context - Sinkkonen, Elina (Cambridge University Press (CUP), 2025)
There is tension between manipulation of national identity construction and agency in the literature on ingroup identification, especially in authoritarian contexts. In China, the past is very relevant with regards to legitimacy of the Communist Party. Yet, we cannot just assume that what the state propagates is what can also be found at the bottom-up level. This article analyses social representations of history in China combining the top-down perspective of state education policies and curated historical narratives to the bottom-up perspective formed through analyzing two student surveys, collected first in 2007 and again in 2011-2012, and 11 interviews. Earlier research indicates that in most countries representations of history concentrate on negative issues and their time span is short. Chinese representations of history are divided into narratives of glory and humiliation, and respondents have a much longer perspective to national history than typical participants in international surveys. Finally, although problematic periods such as the Cultural Revolution get less coverage in political speeches and school textbooks, they are not forgotten among students. Furthermore, the view that people should have their own ideas about history and China rather than having to adopt the government promoted narrative was visible in multiple student interviews.